Kajian Bhagavad Gītā Terhadap Makna Prasadam Bagi Masyarakat Hindu di Bali - Ida Bagus Subrahmaniam Saitya; Ni Gusti Ayu Nyoman Meilani (Sphatika: Jurnal Teologi, 2021)
Prasadam in Hinduism is a term in Sanskrit which means God's gift, which is the result or remnant of an offering to Ida Sang Hyang Widhi Wasa who has been purified. In the Hindu community in Bali the term lungura/surudan is better known than the term prasadam. Related to the phenomenon of prasadam, after being investigated, it turns out that the term lunguran/surudan indicates the strata or class of a dish that starts with the offering (bebanten), complete with food, after being offered, the contents of the bakuten turn into lunguran/surudan, which is ready to be enjoyed as a form of grace from Ida Sang Hyang Widhi or Ida Bhatara-Bhatari who has been presented with a sincere heart and has sacred values and is meaningful as prasadham (holy dish). The Bhagavad Gītā states that, those who eat holy food after going through an offering or sacrifice will attain eternal Brahman (God). So there is no reason to think, whether to accept or desire to refuse the blessings of the blessing of Prasadam, because it has previously been offered as a sacred dish for Ida Sang Hyang Widhi Wasa and His manifestations.